Sex Gender Becoming: Post-Apartheid Reflections - Karin van Marle (Pretoria University Law Press (PULP), 2006)
About the publication All the chapters in this volume in one way or another reflect on change and transformation and how these changes/ transformations affect our sexed and gendered lives. The continuance of binaries, and objectifications and the maintenance of patriarchy notwithstanding these changes are teased out in various themes by the different authors. The contributions expose also how new approaches to how we live sex and gender do not necessarily manage to break or even radically challenge the old. From new technologies that can 'transform' gender, to new forms of pornography, freedom of sexual orientation, the creation of shopping malls, attempts to understand reproductive choices, restorative justice as response to sexual violence, women's testimonies, and women's mobility - all attempts are still hindered by conventional frameworks, structures and thought. A central call that emerges from all the contributions is one for more theory and more gender sensitive research and more listening to previously silenced voices. Comments from the reviewers: From the discussion of 'gentleman's pornography' to the consideration of women's travel needs in a development context, and Stephen Cohen's performance art, the contributions are firmly anchored in our own context and frame of reference. - Louise du Toit, University of Johannesburg I would like in conclusion to remark that the standard and academic merit of the contributions to this book bodes well for gender research in South Africa in future. - Irma Kroeze, Unisa About the editor: Karin van Marle is Professor at the Department of Legal History, Comparitive Law and Jurisprudence, at the Faculty of Law, University of Pretoria.